2008
DOI: 10.1590/s0004-282x2008000200018
|View full text |Cite
|
Sign up to set email alerts
|

Oligosymptomatic dengue infection: a potential cause of Guillain Barré syndrome

Abstract: -Background: Dengue infection may cause neurological manifestations such as encephalitis, myelitis, mononeuropathies, acute disseminated encephalomyelitis, and Guillain Barré syndrome (GBS). In endemic regions, the infection course can be oligosymptomatic making difficult the diagnosis of the neurological picture associated with dengue infection. Objective: To report dengue infection and GBS association, even in oligosymptomatic cases of this infection. Method: During the dengue epidemic in Rio de Janeiro city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…According to the authors, dengue infection should be routinely looked for in Guillain barre syndrome cases in an endemic zone. [18]…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, dengue infection should be routinely looked for in Guillain barre syndrome cases in an endemic zone. [18]…”
Section: Discussionmentioning
confidence: 99%
“…4 However, dengue infection may have been underestimated as a causative agent of GBS. 5 It is suggested that the clinical manifestations of GBS are the result of cell-mediated immunological responses to nonself-antigens (infectious agents, vaccines) that misdirect to host nerve tissue through a resemblance of epitope (molecular mimicry) mechanism. 3,6 The activated T cells cross the vascular endothelium (bloodbrain barrier) and recognize an antigen in the endoneural compartment.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, dengue infection may have been underestimated as a causative agent of GBS. 40 The authors reported seven cases (46.6% of all included GBS cases), presenting with dengue positive IgM in serum but with little to no clinical symptoms of the previous infection. The neurological picture of GBS cases induced by dengue infection is similar to that described in the literature concerning GBS caused by other infections in which ascending paraparesis is the principal manifestation.…”
Section: Guillain Barré Syndrome and Mononeuropathiesmentioning
confidence: 99%